What every pianist needs to know about the body : a manual for players of keyboard instruments : piano, organ, digital keyboard, harpsichord, clavichord - Mark, Thomas Carson, 1941-; Gary, Roberta; Miles, Thom; Conable, Barbara (Chicago : GIA Publications, 2003)
Techniques on how to gain greater fluidity of movement while playing to improve the quality of the experience are offered in this manual for serious piano players. This book encourages musicians to develop a broader understanding of the involvement of the entire body in playing-and the strains playing places on the body-by focusing on body mapping to increase awareness of the body's function, size, and structure. Ways in which piano, organ, harpsichord, clavichord, and digital keyboard players can eliminate or prevent carpal tunnel syndrome and other debilitating conditions without traditional medical treatments are also explored
-- Basic concepts -- Mapping the structure -- Mapping the places of balance -- Mapping the arm and hand -- Mapping muscles -- Mapping breathing -- Mapping the piano -- Additional concerns of organists -- Injuries and retraining
"Based on What every musician needs to know about the body, by Barbara Conable."
Includes bibliographical references (page 153)
Keywords: Keyboard instruments -- Performance -- Physiological aspects; Keyboard players -- Health and hygiene; Piano -- Performance -- Physiological aspects; Pianists -- Health and hygiene